SO2 oxidation in a periodically operated trickle bed: Comparison of activated carbon catalysts - Lee, JK; Hudgins, RR; Silveston, PL (AMER INST CHEMICAL ENGINEERS, 1996)
Catalytic activities of two different activated carbons, BPL(TM) and Centaur(TM) catalysts (Calgon Carbon Corp), were compared in a periodically operated trickle-bed reactor for SO2 oxidation by varying the cycle period and split. In an effort to characterize the carbon surface, differential thermogravimetric analysis and TPD were used to observe oxygen functional groups. The Centaur catalyst, which appears to have a more suitable density of oxygen functional groups, has the higher catalytic activity for SO2 oxidation.
Keywords: PYROLYSIS; REMOVAL; REACTOR